Kajian Praktik Money Laundering dan Tax Avoidance dalam Transaksi Cryptocurrency di Indonesia - Saputra, Raihan; Ramadani Silalahi, Purnama (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Cryptocurrency is the name used for a system in cryptography, which is used in the process of releasing data securely and to carry out the process of changing digital tokens in a dispersed manner. This research applies normative legal research methods. Based on the research conducted, it was found that the case of money laundering in cryptocurrency occurred because of the anominity feature where the real identity cannot be tracked and protected by the system. So that there is a gap to commit crimes such as money laundering. However, based on the data presented in the case of money laundering in cryptocurrencies, it has decreased due to cooperation between platforms/exchangers and PPATK to minimize the occurrence of such cases. It can be concluded that tax reporting on cryptocurrency profits must be reported and is not difficult for the procedure.